On the Determinants of Cloud Computing Adoption - Jörg Ohnemus; Thomas Niebel (International Telecommunications Society (ITS), 2016)
Cloud computing is widely seen as a new source of innovation as well as a driving factor of productivity improvements of firms. This paper analyses the determinants of cloud computing adoption in general as well as for specific deployment (Public vs. Private) and service models (SaaS, IaaS, PaaS). Our data set contains a representative sample of 2,970 German firms and refers to the years 2014 and 2015. The econometric analysis confirms our three main hypothesis regarding firms' decision to adopt cloud computing in general. The share of workers with mobile internet access, being a start-up, as well as the regional availability of high-speed fixed-line internet access increase the likelihood of a firm for using cloud computing services.
Keywords: L10; L86; O33; 330; Adoption of ICT; Cloud Computing; Multivariate Probit